Bifidobacterium components have immunomodulatory characteristics dependent on the method of preparation - Hiramatsu, Yasuhiro (Springer Netherlands, 2007)
Some bifidobacteria or lactobacilli exhibit a variety of immunomodulatory effects, such as being anti-inflammatory, increasing IgA secretion, and moderating allergy. We prepared three types of Bifidobacterium components from B. pseudocatenulatum JCM 7041 (Bp) using preparation methods such as sonication, heat treatment, and non-treatment (live Bp). Furthermore, we compared their immunomodulatory effects using in vivo and in vitro immunological bio-assays. We determined immune responses such as cell proliferation and the production of cytokines and IgA in Peyer’s patch cells in vitro following co-culture with bacterial components, and investigated the effects of oral administration of each of them on cytokine and IgA production by Peyer’s patch cells. Live-, ultrasonic treated- and heat-treated Bp exhibited cytokine-inducing and cell proliferation activities. Sonicated Bp in particular showed the greatest immunomodulatory activity in the short term as measured by in vitro and in vivo assays, while heat-treated Bp induced cytokines (e.g. IL-6 and IFN-γ) and IgA production following oral administration for 7 consecutive days. These data showed that Bifidobacterium components prepared by different methods might induce different immune responses. Using scanning electron microscopy we demonstrated that the surface structure of sonicated Bp, which contained more soluble saccharides, was different from other components. These data suggest that the immunomodulatory effect of Bp is dependent upon the bacterial conformation and condition.